Efektivitas Program Penanganan Covid-19 dan Pemulihan Ekonomi Nasional (PC-PEN) ditinjau dari Ekonomi Pancasila - Rachel, Francesca; Hanifa, Shafa Andien; Akbar, Wafa Raniah Putri (Maliyah : Jurnal Hukum Bisnis Islam, 2022)
The COVID-19 Pandemic that has lasted for 2 years has resulted in a weakening of the economy in Indonesia. The formation of various policy strategies by the Government to overcome these conditions has been carried out based on the values espoused in the Pancasila Economic System. This system is expected to provide solutions in dealing with challenges and conditions during the pandemic. This solution is realized in extraordinary steps, one of which is the Economic Recovery and Structural Reform which is in line with the Covid Handling and National Economic Recovery (PC-PEN) program. The theme of the Government Work Plan (RKP) in 2022 is Economic Recovery and Structural Reform which is in line with the PC-PEN program which has been ongoing since 2020. Based on Law No. 2 of 2020 concerning Stipulation of Perppu No. 1 of 2020 concerning State Finance Policy and Financial System Stability for Handling the Covid19 Pandemic and/or in Facing Threats That Endanger the National Economy and/or Financial System Stability Becomes Law, with the focus on the budget for the PC-PEN program as a form of economic recovery, widening the APBN deficit above 3 percent of GDP is allowed until 2022. The government through the fiscal and monetary authorities prepares strategic steps for a soft landing and exit strategy in financing the national economic recovery based on people's welfare. This writing was made with a qualitative approach that aims to analyze the effectiveness of the Covid-19 Handling and National Economic Recovery (PC-PEN) program after the COVID-19 Pandemic by referring to the Pancasila values.